STRATEGI PENINGKATAN DAN PEMANFAATAN LAYANAN SPBE KETENAGAKERJAAN STUDI KASUS APLIKASI BEBUNGE KABUPATEN BEKASI - Khoerunnissa Putri Syahdani; Indra Aditya; Gun Gun Gumilar (LPPM Universitas Abdurrab, 2026)
This study aims to examine the strategies implemented by the Department of Manpower in utilizing and enhancing employment SPBE services, namely AK1 or digital yellow cards integrated into the Bebunge application. The method used in this study is qualitative with a case study approach. Data collection techniques include field observation, in-depth interviews, and documentation. The results of the study indicate that the strategies carried out by the Bekasi Regency Department of Manpower, reviewed through indicators of organizational strategy, programs, supporting resources, and institutions according to Koteen (1991), are able to improve the accessibility and efficiency of AK1 services. Although there are still network and administrative obstacles, service innovations such as chat features and mobile BOTRAM services expand the reach of services for job seekers. These findings indicate that an integrated strategy based on cross-regional collaboration plays an important role in improving the quality of digital-based public employment services.